DETERMINATION OF THE AMOUNT OF CHLOROPHYLL IN SOLANUM NIGRUM PLANT LEAVES INFECTED WITH POTATO Y VIRUS AT DIFFERENT LEVELS - Nasiba Ibrahimna Shonazarova (Galaxy International Interdisciplinary Research Journal, 2022)
In this article, potato viruses, their types, Potato Y virus (KYV) strains, their biological characteristics, disease symptoms in host plants and their specific aspects, ituzum (solanum nigrum) infected with the virus to different degrees using mechanical methods are discussed. The amount of chlorophyll pigment in the leaves of the wire, the level of study, distribution and importance of these viruses are reflected.